Reconstitution of social work : towards a moral conception of social work practice / editors, Yuk-ying Ho, Sun-pong Yuen. - Ho, Yuk-ying (Singapore ; Hackensack, N.J. : World Scientific Pub. Co., c2010., 2017)
xxv, 272 p.